USING POPULAR CULTURES MEDIA OF INDONESIAN - ENGLISH PICTUREBOOKS AS A WAY OF REACHING MORE VEGETABLE CONSUMING CHILDREN - Ekawati Marhaenny Dukut; Maya Putri Utami; Adi Nugroho; Novitai Ika Putri; Probo Y. Nugrahedi (Soegijapranata Catholic University, 2014)
A questionnaire and interview recently given to 5-8 year old children and their parents show that consumption of vegetables is low. One of the factors for the low consumption is due to the lack of creativity in making various menu and creative media to obtain children?s interest in wanting to consume vegetables. In Indonesia, if young children can be taught to actively use the English language, it will be a great advantage for their future?s education. Based on these backgrounds, through the various media available in today?s popular culture, picturebooks that can increase children?s ability to read English language texts in addition to consume vegetables is created. A picturebook project is regarded highly relevant for teachers who specialize in English language, visual communicative design and food technology. This article shares how with a bilingual picturebook, a reader will know how to pronounce the English language well because there is a phonetic transcription guide provided at the back of the book. Also at the back of the book is a menu for the vegetable that becomes the main character of the book. With this strategy, the book is projected to be popular to readers who want to also create attractive vegetable menus for children. The picturebook that is packed with simple yet interesting visual language is also a way to show how creative one can be in designing lovable vegetable characters. This article discusses the reasonings of creating the picture book.